Vaksinasi dan Digitalisasi Komunikasi Kesehatan (Studi Fenomenologi Interpretatif atas Pemahaman Pengguna Platform PeduliLindungi di Yogyakarta) - Narwaya, Tri Guntur; Lestari, Rani Dwi (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2024)
The development of “PeduliLindungi” Application is one of the government's efforts to respond to the COVID-19 pandemic. The government designed this application to track and detect the potential spread of the SARS-CoV-2 virus so that it does not spread further. Recording vaccinations, history oaf exposure to viruses, and personal health status in this application is personal data that can be used stakeholders related to getting an idea of a person's condition or health status. The “PeduliLindungi” application become a real picture of the progress of digital-based health communication. Using this application during the Covid-19 pandemic has become an obligation for everyone if they want to access public services. Through an Interpretative Phenomenology analytical study approach developed from the ideas of Georg Gadamer's Hermeneutics, researchers attempt to explore further the understanding and meaning of the use of “PeduliLindungi” application in implementing the vaccination program as a mitigation measure for handling the Covid-19 outbreak in the city of Yogyakarta. The target subjects of this research are all user of “PeduliLindungi” application in Yogyakarta. The users of “PeduliLindungi” application, especially those survivors who have been infected with Covid-19. The research results show that there is a tendency for the subject's understanding of “Peduli Lindungi” application development only as an instrument of health communication with all the ethical risk consequences therein. The use of applications is more related to procedural formalities and is not based on awareness of choice because health aspects are fully considered. Communication in the “PeduliLindungi” application could be said that it has not yet formed an understanding but is limited to being a means of control over the individual's body.ABSTRAKPengembangan aplikasi PeduliLindungi menjadi salah satu upaya pemerintah merespon pandemi COVID-19. Pemerintah merancang aplikasi ini untuk melacak serta mendeteksi adanya potensi penyebaran virus SARS-CoV-2 agar tidak semakin meluas. Pencatatan vaksinasi, riwayat terpapar virus, dan status kesehatan personal dalam aplikasi ini menjadi data pribadi yang bisa dimanfaatkan stakeholders terkait untuk mendapatkan gambaran kondisi atau status kesehatan seseorang. Aplikasi PeduliLindungi menjadi gambaran nyata dari wajah kemajuan komunikasi kesehatan berbasis digital. Penggunaan aplikasi ini dalam masa pandemi Covid-19 bertransformasi menjadi kewajiban bagi setiap orang jika mereka ingin mengakses layanan publik. Melalui pendekatan kajian analisis Fenomenologi Interpretatif yang dikembangkan dari gagasan Hermeneutika Georg Gadamer peneliti berupaya untuk menggali lebih lanjut mengenai pemahaman dan pemaknaan atas pemanfaatan aplikasi PeduliLindungi dalam pelaksanaan program vaksinasi sebagai langkah mitigasi penanganan wabah Covid-19 di kota Yogyakarta. Subjek sasaran dari riset ini adalah para pengguna aplikasi PeduliLindungi, terutama mereka para penyintas yang pernah terinfeksi Covid-19. Hasil riset menemukan bahwa ada kecenderungan pemaknaan subjek terhadap aplikasi PeduliLindungi hanya sebatas sebagaai instrumen formalitas karena bertujuan memenuhi aturan SOP semata. Penggunaan aplikasi lebih banyak terkait dengan formalitas prosedural dan tidak didasari oleh kesadaran pilihan karena pertimbangan aspek kepentingan kesehatan. Komunikasi melalui aplikasi PeduliLindungi bisa dikatakan belum membentuk ‘kesepahaman’ namun sebatas menjadi instrumen kontrol atas tubuh individu.